Work Motivation and Job Satisfaction of Teachers: An Assessment - Maharjan, Sarita (PYC Nepal Journal of Management, 2012)
This paper examines the association between work motivation and job satisfaction of teachers. With convenient sampling technique, only 112 responses are usable out of 150 questionnaires distribution to the teachers of university constituent, affiliated and plus two campuses/ colleges in Kathmandu valley. Using descriptive statistics and correlation analysis, the study analyses the work motivation and job satisfaction of the teachers. The study concludes that there is a positive association between work motivation and job satisfaction of teachers.